PENGEMBANGAN PERANGKAT PEMBELAJARAN BTL (BETTER TEACHING AND LEARNING) UNTUK MENGEMBANGKAN KEMAMPUAN BERPIKIR KREATIF DAN KARAKTER SISWA SMP (UPEJ Unnes Physics Education Journal, 2013)
One of the aim of sains learning is to develop thinking skill. BTL model or meaning learning is developed to train life skill. One of the skill that has to be mastered by students is thinking skill. The aim of the research is developing BTL model to develop creative thinking skill and student’s character at heat subject and to know the developmentcreative thinking skill and also student’s character of responsibility, discipline, curiousity, and communicative. The research’s subject is VII H students of SMP N 3 Semarang at academic year of 2012/2013. This study is a research and development of quasi-experimental design type design pre-test and post-test one group.Validation product test is done by supervisor. Products produced are learning instrument, such as syllabus, lesson plan with integration of character value, work sheet arranged by creative thinking skill’s aspects and assessment sheet. The research result shows the development of BTL model can develop student’s creative thinking skill and character of heat subject.